Gestión administrativa - financiera y su incidencia en el rendimiento financiero de la urbanización ciudad verde, Santo Domingo, periodo 2011-2013, plan de mejoras continua. - Guerrero Cruz, Lucy Viviana (2015)
The increasing demand for housing by families of middle and low socioeconomic status is driving the country's property market. The support for home purchase by this group of families is given by several related countries to social housing, which has been implemented in a big way in recent years in Latin American countries, in the case of Ecuador, the Government gives the Housing bonus coordinated with MIDUVI as a reward for their efforts to save; It serves to: buy a house, build it when the family has land or improve it if the applicant already has one. According to the Housing Ministry for the year 2013 the bonus was USD $5,000.00 and the price of housing should be a maximum of USD $ 20,000.00 to receive the bonus, the Government wants to implement in the beneficiary families and aspirants the SBC (ABC) that means: SAVING + BONUS + CREDIT = home. There are approximately more than 10 housing complexes In the city of Santo Domingo these are located in different areas of the city, two of them have social housing, hoses with cost for families of low and middle socioeconomic social status, one of them is the Construction “Ciudad Verde”, which was founded in 2007 and its studies revealed that there are groups of underserved families in these socioeconomic levels. Among the main objectives of “Ciudad Verde” Construction for this segment of families is: to provide a better lifestyle, quality of construction, access to public and private services that demanded by a dignified complex. In Ciudad Verde urbanization the administrative and financial management is handled by its owner and employees, who are responsible for the fulfillment of the objectives previously planned, activities and the implementation of control systems, for this reason in the present research was carried out a study to determine whether the administrative financial management affects the financial performance of Ciudad Verde complex.